2012
DOI: 10.1002/adfm.201102222
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Nanocomposites Derived from Nanocarbons and Layered Double Hydroxides ‐ Properties, Synthesis, and Applications

Abstract: A good arrangement and construction of different low-dimensional nanomaterials (e.g., zero-dimensional (0D) nanoparticles (NPs), one-dimensional (1D) nanotubes, nanowires, nanorods, and two-dimensional (2D) flakes) as building blocks with two or more levels from the nanometer to the macroscopic scale leads to the formation of three-dimensional (3D) hierarchical nanocomposites. Hierarchical composites are widely observed in nature, e.g., in plant cell walls, bone, animal shells, and skeletons, showing that a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
311
0
17

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 559 publications
(333 citation statements)
references
References 194 publications
1
311
0
17
Order By: Relevance
“…Moreover, some research works appeared on the possible recovery of adsorbates, such as As(V), 3 4 PO − and Cr(VI) from spent LDHs [75,96,97]. Gillman [96] reported that the minute amount of As in the As-loaded LDHs could be easily recovered by saturating As-loaded LDHs with phosphate, while Kuzawa et al [95] proposed a scheme whereby the desorbed 3 4 PO − in the spent desorption solution could be recovered as calcium phosphate precipitate by addition of CaCl 2 , and the remaining spent desorption solution could also be reused after supplementing additional NaOH ( Figure 5) [98,99].…”
Section: Heave Metal Capture In Liquid Wastementioning
confidence: 99%
“…Moreover, some research works appeared on the possible recovery of adsorbates, such as As(V), 3 4 PO − and Cr(VI) from spent LDHs [75,96,97]. Gillman [96] reported that the minute amount of As in the As-loaded LDHs could be easily recovered by saturating As-loaded LDHs with phosphate, while Kuzawa et al [95] proposed a scheme whereby the desorbed 3 4 PO − in the spent desorption solution could be recovered as calcium phosphate precipitate by addition of CaCl 2 , and the remaining spent desorption solution could also be reused after supplementing additional NaOH ( Figure 5) [98,99].…”
Section: Heave Metal Capture In Liquid Wastementioning
confidence: 99%
“…Various methods have been explored to overcome these problems, such as the combination of LDH with carbon nanofibers [14] and carbon nanotubes [15][16][17][18][19][20], as previously studied in our group [21]. Among the nanocarbons, the 2D geometry of graphene oxide (GO) is obviously compatible with the layered structure of LDHs and there is also a charge compatibility between the positively charged LDH and negatively charged GO.…”
Section: Introductionmentioning
confidence: 99%
“…Among the nanocarbons, the 2D geometry of graphene oxide (GO) is obviously compatible with the layered structure of LDHs and there is also a charge compatibility between the positively charged LDH and negatively charged GO. The large size of GO sheets compared to LDH platelets implies that it may be possible to form an open network with large pores allowing access of the reactants to the active LDH sites which is helpful for the high rate conversion of the reactants [15]. When combining LDH with GO, the heat and mass transfers during a reaction can be greatly improved.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Owing to the specific structure and versatility in chemical composition, LDHs have been widely used as multi-functional materials in the fields of photocatalytic water splitting and degradation of environmental pollutants etc. [16,17] Previous work have demonstrated that the intercalation of polyoxometalates (POMs) into LDHs inter-lamellar gallery can effectively depress the aggregation, enhance the dispersion and stability of the guests. [18][19][20][21][22] Most importantly, compared with other immobilized systems such as SiO2/POMs, ZrO2/POMs, Al2O3/POMs etc, the LDHs/POMs nanocomposites would exhibit the following advantages: (1) the host-guest interactions (e.g., electrostatic, van der Waals, or hydrogen bonding) induce a homogeneous distribution of POMs guests at the molecular level; (2) the chemical stability and photo-stability of POMs can be largelyimproved by the introduction of inorganic LDH component; (3) the POM-leaching issue for many heterogeneous catalysts is not pronounced after intercalation.…”
Section: Introductionmentioning
confidence: 99%